2016
DOI: 10.1097/mca.0000000000000401
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of coronary artery dilation response to nitrate for a positive intracoronary acetylcholine provocation test

Abstract: Coronary artery dilation response to nitrate is a more accurate predictor of a positive intracoronary ACh provocation test compared with baseline coronary artery diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Compared with the previous studies 9 , 10 , our study has several advantages. First, our analysis was conducted with a relatively large number of patients who were enrolled consecutively.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Compared with the previous studies 9 , 10 , our study has several advantages. First, our analysis was conducted with a relatively large number of patients who were enrolled consecutively.…”
Section: Discussionmentioning
confidence: 87%
“…In this regard, some researchers have introduced simpler methods for the diagnosis of vasospastic angina. In one retrospective study, the predictive value of NID for a positive acetylcholine provocation test was evaluated 9 . The authors of this study concluded that NID is a possible predictor for a positive result of the acetylcholine provocation test.…”
Section: Discussionmentioning
confidence: 99%